Penyajian dan Pemorsian Makanan Pokok pada Penyelenggaraan Makan Pasien Anak di RSA UGM - Mrs Istiyaningsih; Titik Sulistyani; Prihatin Saraswati (Jurnal Socia Akademika, 2020)
This research aims to determine the process of serving and screening of staple food in the feeding of child patients in nutrition installation of RSA UGM. This research includes a type of qualitative research because the research is being discredited and tends to use a discrete analysis. In this study, the study subject determination is determined by sampling technique, while the object being studied is the presentation and food preparation in the feeding of child patients. Data collection techniques are conducted with interviews, observations and documentation. Interviews and observations are used to obtain data that contains details – details on basic food presentation and screening, in the standard size correction of food portions have been determined by nutritionists, but the officers of the Pemorsi only thought – he and patting the size of the rice mould when rice printed weighing 200 grams, while the documentation is used to describe the real shape during the process of serving and food delivery of photographs. The Data is analyzed by a descriptive analysis technique. Results of the analysis showed that the food delivery of the children's diet is less attractive and the standard size of the basic food portion is determined by the nutritionist, but the officers or presenters do not weigh the staple food.